Retirement Migration: The Malaysia My Second Home (Mm2h) Program And The Japanese Retirees In Penang - Guan, Benny Teh Cheng (Penerbit Universiti Sains Malaysia (USM Press), 2018)
Modernisation and easy connectivity across spatial boundaries are providing greater opportunities for retirees to migrate abroad. In Malaysia, the Malaysia My Second Home (MM2H) program has been gaining popularity over the last 14 years. It is a government initiative designed to promote the country as a retirement haven for afﬂuent foreigners. By studying the Japanese retirement community in Penang, this paper examines the role and signifcance of the program in supporting retirement migration. It further identifes the concerns and contributions of the Japanese retirees as they build their “second lives” in Penang. While the MM2H program has undergone several enhancements, discussions on the experiences of the Japanese participants and research observations have highlighted several concerns that require further improvements. The lack of policy coordination between the various sectors catering to the expanding needs of foreign retirees, for example, reduces the chances of maximising participants’ contribution to the local economy. The ability to track and monitor the movement of participants is equally, if not more, important as promoting and enticing new ones